2015
DOI: 10.1136/bmjopen-2014-005803
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a prospective cohort of mechanically ventilated patients in five intensive care units in Lima, Peru: protocol and organisational characteristics of participating centres

Abstract: IntroductionMechanical ventilation is a cornerstone in the management of critically ill patients worldwide; however, less is known about the clinical management of mechanically ventilated patients in low and middle income countries where limitation of resources including equipment, staff and access to medical information may play an important role in defining patient-centred outcomes. We present the design of a prospective, longitudinal study of mechanically ventilated patients in Peru that aims to describe a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…None of the five ICUs participating in this study used protocols for sedation management, nor did they use tools to screen or manage delirium [17]. This is not surprising since data from previous international surveys reported implementation rates between 20% and 80% [1], including a study of 912 ICU practitioners in high-income countries that revealed that only 16% used a valid delirium assessment tool [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the five ICUs participating in this study used protocols for sedation management, nor did they use tools to screen or manage delirium [17]. This is not surprising since data from previous international surveys reported implementation rates between 20% and 80% [1], including a study of 912 ICU practitioners in high-income countries that revealed that only 16% used a valid delirium assessment tool [30].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the protocol and participating ICUs was provided elsewhere [17]. Adults with acute respiratory failure were consecutively screened in a longitudinal, observational study in five ICUs at four public hospitals in Lima, Peru.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no established ventilation protocols in use at the Peruvian ICUs; ventilator settings are based on intensivist preference. Details of the characteristics of the participating ICUs and their organization and structure are described elsewhere [22]. We received ethics approval and permission to conduct this study in each of the participating institutions: Hospital Nacional Edgardo Rebagliati Martins, Hospital Nacional Guillermo Almenara Irigoyen, Hospital Nacional Arzobispo Loayza, and Hospital de Emergencias Casimiro Ulloa.…”
Section: Methodsmentioning
confidence: 99%
“…Secretion clearance is usually used to keep the respiratory tract clear and to improve alveolar ventilation and patients' breathe function. Thus, secretion clearance is one of the most important nursing interventions of ventilated patients' respiratory tract 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%